The fascist temptation - Ohana, David, author.
1 online resource.
Keywords: "This book posits new a theory of fascism as a radical political community of experience. The author engages with a range of thinkers both critical of and inspiring fascism including Walter Benjamin, Albert Camus, Ernst Jünger, Carl Schmitt, Friedrich Nietzsche and Martin Heidegger. This book will be of interest to scholars of the history of political thought, fascism and Nazism"--